Rancang Bangun Website Sekolah Untuk Peningkatan Kapasitas Sekolah Dasar Negeri Menjadi Sekolah Adiwiyata, Terakreditasi dan Role Model Di Balikpapan Tengah - Ihsan Ihsan; Nur Yanti; Dwi Lesmideyarti (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
The world of education, from elementary school to university levels, is required to be able to adapt to the progress of science and technology that is growing so rapidly, especially in the field of information. And the current state of the Covid-19 pandemic requires every institution to help reduce the number of its spread. One of the lines of society affected by COVID-19 is schools, especially elementary schools that do not yet have school website facilities as a medium of information to the public. In this community service activity, the implementing team designed the website for the SDN 020 Central Balikpapan school as a partner. The problems faced by partners are the location of schools that are not strategically located in the Central Balikpapan area, not having informative media for various aspects of interest, the existence of an online PPDB policy from the Education Office to suppress the spread of Covid19, To overcome these problems, SDN 020 Central Balikpapan must have websites. The benefits of online PPDB activities can be carried out so that parents do not need to go to school during registration, can meet the requirements as an Adiwiyata school, and can facilitate the achievement of school accreditation. The method of implementing community service activities by the team consists of building communication with partners, designing school websites, providing training on the use of websites in the form of filling out content and managing databases, implementing websites in schools, socializing school websites to the community, maintaining and repairing websites after implementation. This series of community service activities is planned for a maximum of 8 months. The service activity took place successfully and could help school operators in data processing and selecting prospective students easily and quickly